Identifikasi Adaptasi Psikologis Masyarakat Lombok Tengah Pada Era New Normal - Purqoti, Dewi Nur Sukma; Oktaviana, Elisa; Amrullah, Muhammad (Universitas Qamarul Huda Badaruddin, 2020)
The Covid-19 outbreak in Indonesia has been going on for approximately four months. Various policies have been implemented by the government to overcome this pandemic, ranging from the application of social distancing, physical distancing, urging people to always use masks when leaving the house, dismissing schools and workplaces, limiting religious activities and limiting activities in public areas, to social restrictions on a scale big. The various impacts felt by the community in terms of health, social, economic, education, politics and development, this is what causes psychological pressure on the community. The purpose of this study is to determine the description of the psychological adaptation of the people of Central Lombok in the new normal era. descriptive method quantitative analysis with cross sectional approach. From the results of the study, the average respondent in this study was 18 to 55 years old, the majority sex was male as many as 34 people (63%), the most education was higher education with a number of 27 people (50%), most of whom worked as entrepreneurs. 31 people (57.4%), the majority of the marital status was in the married category of 31 people (57.4%) and the average respondent in this study had psychological adaptability in the adaptive category as many as 48 people (88.9%).